Exploring vasculogenesis in the normal human kidney and clear cell renal cell carcinoma: insights from development to tumor progression and biomarkers for therapy response - Cosma, Andrei Alexandru; Fenesan, Mihaela Pasca; Nesiu, Alexandru; Melnic, Eugen; Ferician, Adela Maria; Ferician, Ovidiu Catalin; Ceban, Emil; Sarb, Simona; Cimpean, Anca Maria (Frontiers in Oncology, 2024)
Vasculogenesis, which refers to the development of blood vessels from precursor cells, is a process that occurs predominantly during early embryonic life. It plays a crucial role in the establishment of the primitive vascular network. Vasculogenesis diminishes throughout the fetal vascular remodeling process, giving way to angiogenesis, which becomes the predominant mechanism after birth. At first, the development of the kidney's blood vessels depends on vasculogenesis, and then both vasculogenesis and angiogenesis happen simultaneously. Both processes are necessary for the normal development of the renal vasculature. Although the kidneys are highly vascularized, our understanding of normal kidney vasculogenesis is still incomplete. This lack of knowledge may explain the limited data available on the role of vasculogenesis in the progression and spread of renal cancers.